2008
DOI: 10.1002/ijc.24039
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell‐free screen identifies a potent inhibitor of the Fanconi anemia pathway

Abstract: The Fanconi Anemia (FA) DNA damage response pathway is involved in the processing of DNA interstrand crosslinks (ICLs). As such, inhibition of the FA pathway could chemosensitize FAcompetent tumor cells to commonly used ICL agents like cisplatin. Moreover, suppression of the FA pathway is synthetic lethal with deficiencies in several other DNA repair pathways, suggesting that FA pathway inhibitors could be used in targeted therapies against specific tumors. To identify such inhibitors, we designed a novel in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 42 publications
(76 reference statements)
1
48
0
Order By: Relevance
“…Cell-free Xenopus extracts can be obtained in large quantities, are easily activated in vitro, and can recapitulate important cellular processes such as cell cycle progression, DNA replication, and centrosome duplication in vitro. Given these properties, it is not surprising that cell-free extracts from Xenopus have been used successfully in chemical screens to identify small-molecule modulators of actin assembly, microtubule stability, ubiquitin-dependent protein degradation, cell cycle machinery, and DNA damage response (Verma et al, 2004;Wignall et al, 2004;Dupre et al, 2008;Landais et al, 2009). Chemical screening in cellfree Xenopus egg extracts takes place in a fully soluble in vitro context.…”
Section: Using Cell-free Xenopus Extracts For Chemical Screensmentioning
confidence: 99%
“…Cell-free Xenopus extracts can be obtained in large quantities, are easily activated in vitro, and can recapitulate important cellular processes such as cell cycle progression, DNA replication, and centrosome duplication in vitro. Given these properties, it is not surprising that cell-free extracts from Xenopus have been used successfully in chemical screens to identify small-molecule modulators of actin assembly, microtubule stability, ubiquitin-dependent protein degradation, cell cycle machinery, and DNA damage response (Verma et al, 2004;Wignall et al, 2004;Dupre et al, 2008;Landais et al, 2009). Chemical screening in cellfree Xenopus egg extracts takes place in a fully soluble in vitro context.…”
Section: Using Cell-free Xenopus Extracts For Chemical Screensmentioning
confidence: 99%
“…As such, cells defective in the FA pathway are rendered sensitive to a variety of DNA crosslinking agents, making the FA pathway an attractive target for inhibition in cancer cells. In an attempt to identify novel inhibitors of the FA pathway (FAPi), several groups have carried out large-scale small-molecule library screens [13-16]. These studies have revealed four FAPi that are currently commercially available; curcumin and its monoketone analogues EF-24 & 4H-TTD, and the menadione analogue DDN [13-16].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to identify novel inhibitors of the FA pathway (FAPi), several groups have carried out large-scale small-molecule library screens [13-16]. These studies have revealed four FAPi that are currently commercially available; curcumin and its monoketone analogues EF-24 & 4H-TTD, and the menadione analogue DDN [13-16]. However, the mode of action of these compounds has not been elucidated to date, and curcumin may impact on multiple DNA repair pathways [17].…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of a natural anti-cancer compound, curcumin, to inhibit FANCD2 monoubiquitination, or the synthetic agent wortmannin, which inhibits kinases, such as ATR and ATM, upstream in the FA/BRCA pathway [53]. Aiming to improve the potency and specifi city of these inhibitors, new compounds, such as monoketone, an analogue of curcumin [54], or the naphthoquinone (DDN) [55], have been more recently developed. Similarly, other approaches aim to sensitise head and neck human cancer cell lines to cisplatin by reducing BRCA1 expression with the histone deacetylase inhibitor phenylbutyrate [56].…”
Section: Signifi Cance Of the Fanconi Anaemia Pathway In The Cell Resmentioning
confidence: 98%